Eocene Algae from Ishigaki-shima Ryūkyū-rettō - Johnson, J. Harlan (Jesse Harlan), 1892-1974 (Geology and paleontology of Ishigaki-shima, Ryūkyū-rettō., 1964)
"Descriptions of six new species from exceptionally well preserved specimens of Eocene limestone."